Analisis Penentuan Lokasi Pembangunan Tempat Wisata Pantai di Kecamatan Leitimur Selatan Dengan Penerapan Metode Fuzzy Topsis - Jerry Rieuwpassa; Victor O. Lawalata; D. B. Paillin (ARIKA, 2015)
Beach tourism is one of tourism protections that able to be developed in South Leitimur district. The development of this tourism will increase local income (PAD), community's economic and provide opportunities for external investor to invest on tourism in this district. Since requiring a lot of time, energy and money, a simultaneously tourism development along the beach on this district will face a very difficult challenges. Therefore, a research performs to identify selected criteria of developed location and propose the worthy location to build tourism at that district. By using Fuzzy TOPSIS method, results of analysis recommend Naku's beach as chosen alternative after rated by entrepreneur respondents who has experienced in beach tourism at Ambon Island.